Leadership Rhetoric and Organizational Strategies in the Book Wasiat Renungan Masa Pengalaman Baru by TGKH Muhammad Zainuddin Abdul Madjid - Jumatriadi (Journal of Scientific Studies and Multidisciplinary Research, 2025)
This research examines the leadership rhetoric and organizational strategies within the book Wasiat Renungan Masa Pengalaman Baru by TGKH Muhammad Zainuddin Abdul Madjid. The study aims to analyze how the text conveys principles of leadership and organizational management, emphasizing the relevance of Islamic values and cultural principles. Using a qualitative approach with a textual analysis method, the study investigates key themes related to leadership rhetoric, such as unity, obedience, loyalty, and brotherhood, as well as organizational strategies focusing on collective action, ethical leadership, and resilience. The findings reveal that the text provides timeless guidance on leadership, highlighting the importance of ethical behavior, collective effort, and adherence to spiritual practices. Furthermore, the organizational strategies outlined in the text align with Islamic teachings and Sasak cultural values, offering a framework for modern organizational leadership, especially within Islamic educational institutions. The research contributes to the understanding of Islamic leadership, offering practical insights for contemporary leaders and organizations, promoting the integration of moral and spiritual values into organizational practices.